Ethics And Politics - Irina Patrintas (Politikon, 2002)
This article is centered on the idea of “concentricity” regarding two fundamental concepts that seemed to have become indirect priorities both on the political and the philosophical stages, throughout the centuries: ethics and policy. The main dilemma is represented by an obvious discontinuity between moral principles, which were adopted and implied in the political area, and the way they are understood and respected by the individuals. Is “ethics” an empirical construction, a real term that should be reported to the real existence, not just to the “noumena” universe or is it an utopia, a construct without any appliance in the reality? It cannot be denied that modern societies have tried to adopt these principles, but just from the theoretical point of view; unfortunately, the political field always comes into contradiction with the moral items, although justice and law are founded on ethics. Consequently, a simple, superficial selection of the XXth century’s main violent events proves that no matter how we analyze these theoretical constructions, from a negative or a positive point of view, we develop different theories on major principles, that make the essence of both the political and the philosophical field: liberty, freedom, justice and equality. There also exists a striking discrepancy between the technological progress, which lately has reached incredible standards and levels, and the spontaneous evolution that should have been also requested in the individual’s inward structure, regarding consciousness and responsibility. The modern society confronts itself with another rhetorical question: what has happened to the authentic communication or has it ever existed in real terms? Rawl’s theory of justice and the ethics of communication, in the manner J. Habermas analyzed it, sustains the vital necessity of a minimal consensus among the members of any society. The article presents the hypotheses of this conceptual and empirical conflict.